PARADOXICAL DEPHOSPHORYLATION OF CARDIAC HISTONE DEACETYLASE 5 BY BETA-ADRENERGIC STIMULATION. (21st November 2014) - Weeks, KL; Lewis, H; Karas, A; Ashcroft, AS; Puhl, SL; Avkiran, M
Abstract : Background: Nuclear export of histone deacetylase 5 (HDAC5) promotes cardiac hypertrophy via alleviation of its repressive interaction with the transcription factor MEF2. Some hypertrophic stimuli (e.g. endothelin-1) induce nuclear export via protein kinase D-mediated phosphorylation of Ser259 and Ser498. However, phosphorylation of these residues is not required for nuclear export following beta-adrenoceptor stimulation and Ser279 phosphorylation by protein kinase A (PKA) has been proposed to promote HDAC5 nuclear retention, thereby suppressing MEF2 activity. The aim of this study was to characterise beta-adrenergic regulation of HDAC5 phosphorylation in adult rat ventricular myocytes (ARVM) and in a mouse model of beta-adrenoceptor-mediated cardiac hypertrophy. Methods and results: Stimulation of ARVM expressing GFP-tagged HDAC5 with 10 nM isoprenaline induced a rapid reduction in HDAC5 phosphorylation at Ser259, Ser279 and Ser498, as determ ined by Western blotting of cell lysates with phospho-specific antibodies. Selective activation of PKA with 500 uM N6-benzoyl cAMP had a similar effect. To assess whether such effects occur in vivo, male C57BL/6 mice received subcutaneous infusion of isoprenaline (30 mg/kg/day) or vehicle via osmotic minipumps. Three days of isoprenaline infusion was sufficient to induce cardiac hypertrophy (∼22% increase in heart weight/tibia length, P<0.05, n=7). This was accompanied by reduced phosphorylation of Ser259 and Ser279 relative to total HDAC5 (P<0.05, n=4). Conclusions: Beta-adrenoceptor activation causes dephosphorylation of HDAC5 at Ser259, Ser279 and Ser498 in ARVM, via a PKA-mediated mechanism, and at Ser259 and Ser279 in vivo. Whether such paradoxical HDAC5 dephosphorylation is mechanistically involved in beta-adrenoceptor-mediated induction of cardiac hypertrophy requires further investigation.